The time of expectations and disappointments: displaying new social and political reality in the letters by Russian soldiers from Romanian front (February – April 1917) - Solovyov, Vitaliy V.; Lavrenko, Valeriya S. (Journal of the Belarusian State University. History, 2019)
After the USSR collapse, coming out of October Revolution shadow, the problem of the surrounding reality perception by the First World War soldiers attracts an increasing number of researchers, because it allows a deeper understanding of social and political processes’ nature, which took place in the Russian Empire. And in this regard, the soldiers’ letters are a unique source that allows us synchronizing events at the front with the participants’ attitude towards them. The aim of our study was to reveal the peculiarities of front-line soldiers’ perception of political processes taking place in Russia during February revolution. The work was carried out from the social history point of view and on the basis of microhistorical approach, which involves the study of particular phenomena occurring in the lives of definite individuals of the past, in order to identify the dominant ideas and trends of the society in general. It allowed us realizing the research goals. The «February Report» analysis distinguishes calm moods in the troops and the authors’ of letters confidence in the need to continue the war. There is no doubt that the major culprit for the soldiers’ disasters was the main Russian opponent – Germany. As for the soldiers’ attitude to the socio-political situation change in the country, it is reflected in the report section – The army’s attitude to internal political events. Its materials testify that the main part of soldiers didn’t realize events, which took place at that time. However, the sprouts of revolutionary moods have already given their first shoots. The following March 1917 summary presents us a completely different picture, not like the previous month: high spirits, patriotism, belief in own actions rightness, i.e. the revolution, which took place, had a positive effect on the army’s mood. One can notice confidence in a quick victory over the enemy in soldiers’ letters. At the same time, the number of dramatic changes has being already recorded in the section – «The officer corps’ characteristics» and they were caused by political reforms introduced into the military environment by a new government. The April 1917 summary gives us an opportunity to get acquainted with the soldiers’ perception of reality surrounding them during a period of some emotional sobering, when initial revolutionary passions were somehow declined. And although there still was a large number of letters testifying the soldiers’ conscious awareness of their duty to a motherland, as it could be seen from the Report, the anti-war sentiments were obviously reflected in the military environment. This, in its turn, led to a discipline drop and to an increase of conflicts with the commanders. The authors come to a conclusion that the front-line soldiers’ positive perception of the «new authority» and the political transformations, which were carried out by them, were quickly replaced by a negative attitude towards it, and political reforms led to a decline in discipline and to an increase of anti-war attitudes.
Keywords: letters of veterans; Report censors; military censors; Romanian front; February revolution; Provisional Government